Peningkatan Pengetahuan Masyarakat Desa Timbang Jaya Kecamatan Bahorok Melalui Pelatihan Pembuatan Sabun Cuci Piring sebagai Produk Bernilai Jual - Ahmad Alvin Adriansyah; Mayla Humaira As-syiva; Laksamana Khaidir K N; Widya Ayu Utami Lubis; Heru Syahputra (BADAN PENERBIT STIEPARI PRESS, 2026)
Community service activities took place in Timbang Jaya Village, Bahorok District, Langkat Regency. The aim is to increase the knowledge and skills of residents, especially PKK women, in making dishwashing soap as a household product that has sales value. This activity was motivated by a lack of public understanding about the use of simple materials that can be converted into environmentally friendly products with economic value. The methods used include socialization, training, application of technology, mentoring and evaluation. There were 20 participants who were actively involved in all stages of the activity, from theoretical explanations to direct soap making practice. As a result, participants succeeded in increasing their understanding of the ingredients, manufacturing process, and marketing opportunities for dishwashing soap. They are able to make quality liquid soap with ingredients that are easy to find and at affordable costs. Apart from that, this activity also encourages an entrepreneurial spirit among village communities, especially in developing household businesses based on environmentally friendly products. Thus, this training contributes to increasing economic independence and empowering the Timbang Jaya Village community.